THE INFLUENCE OF LEADERSHIP AND MOTIVATION ON THE PERFORMANCE OF CIVIL SERVANTS AT PALU COURTHOUSE CENTRAL SULAWESI - Marpaung, Darwis D; Miru, Sulaeman; Hasanuddin, Bakrie (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2021)
This study aims to determine the influence of leadership and motivation, simultaneously influencing the employees’ performance at the Courthouse of Palu, Central Sulawesi and the influence of leadership partially on the employees’ performance at the Courthouse of Palu, Central Sulawesi. The population and sample in this study were the entire employees of the Courthouse of Palu, Central Sulawesi which were 60 people. The method of the study applied was descriptive through multiple regression analysis. The results show that leadership and motivation variables simultaneously have a significant influence on the employees’ performance of the Courthouses of Palu, Central Sulawesi, with an R-Square value is 0.611 on sig. 0.000. The leadership variable significantly influences the employees’ performance with a regression coefficient is 0.507 at sig 0.000; motivation notably influences the employees’ performance with a regression coefficient is 0.538 at sig 0.011. Keywords: Leadership, Motivation and Performance